Multi-Stages Synthesis Of Calcium Hydroxide Particles From Malaysian Limestone By Sol-Gel Method - Yong, Rui Huang (Universiti Sains Malaysia, 2022)
The synthesis of calcium hydroxide, Ca(OH)2 from Malaysian limestone via sol-gel method was carried out in this study. Malaysian limestone is high purity raw material that is suitable for production of other calcium based chemical compounds. However, the manufacturing of high purity Ca(OH)2 particles for medical usages was not yet present in Malaysia. Sol-gel method was chosen as the fabrication technique used in this research because sol-gel method has great flexibilities and the procedures are generally simple and cost-saving. The first part of the experiment involved dissolution of CaCO3 with hydrochloric acid, HCl and heat treatment of the product to obtain anhydrous CaCl2 salt crystals. Second part of the experiment involved salt forming reaction between CaCl2 and sodium ethoxide, Na(C2H5O) in ethanol medium. The last step of the experiment is hydrolysis of the Ca(C2H5O)2 solution formed with distilled water into Ca(OH)2 particles and ethanol. The suspension was centrifuged to extract the Ca(OH)2 particles from the solution. The dried sample of Ca(OH)2 was characterized using X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscope equipped with Energy Dispersive X-Ray (FESEM-EDX) and Particle Size Analyser (PSA). Results showed that the synthesized Ca(OH)2 particles have normally distributed particle size with peak at 667.7 nm. They have rod and cornflower mixed morphology with tiny hair-like nanostructures on particle surface as observed under FESEM. XRD result indicated that most Ca(OH)2 had revert into CaCO3 after exposure to carbon dioxide. In short, Malaysian limestone is suitable for synthesis of Ca(OH)2 particles by sol-gel method. Processing parameters showed influence on properties of the product obtained.